Uptake of Epoxydiol Isomers Accounts for Half of the Particle-Phase Material Produced from Isoprene Photooxidation via the HO2 Pathway - Liu, Yingjun; Kuwata, Mikinori; Strick, Benjamin F; Geiger, Franz M; Thomson, Regan J; McKinney, Karena A; Martin, Scot T (Environmental science & technology, 2015)
The oxidation of isoprene is a globally significant source of secondary organic material (SOM) of atmospheric particles. The relative importance of different parallel pathways, however, remains inadequately understood and quantified. SOM production from isoprene photooxidation was studied under hydroperoxyl-dominant conditions for <5% relative humidity and at 20 °C in the presence of highly acidic to completely neutralized sulfate particles. Isoprene photooxidation was separated from SOM production by using two continuously mixed flow reactors connected in series and operated at steady state. Two online mass spectrometers separately sampled the gas and particle phases in the reactor outflow. The loss of specific gas-phase species as contributors to the production of SOM was thereby quantified. The produced SOM mass concentration was directly proportional to the loss of isoprene epoxydiol (IEPOX) isomers from the gas phase. IEPOX isomers lost from the gas phase accounted for (46 ± 11)% of the produced SOM mass concentration. The IEPOX isomers comprised (59 ± 21)% (molecular count) of the loss of monitored gas-phase species. The implication is that for the investigated reaction conditions the SOM production pathways tied to IEPOX isomers accounted for half of the SOM mass concentration.